1994
DOI: 10.1521/pedi.1994.8.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Self-Mutilation and Suicidal Behavior in Borderline Personality Disorder

Abstract: The relationship of self-mutilation to suicidal behavior was studied in 108 borderline inpatients (defined by the Diagnostic Interview for Borderline Patients). Patients with histories of selfmutilation were compared to those with no self-mutilation on diagnostic comorbidity, symptom patterns, prior suicidal be haviors, and attempt characteristics, including number of at tempts, seriousness of intent, and medical lethality.Self-mutilation was found in 63% of patients, suicidal attempts in 75.7%. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
159
0
13

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 13 publications
6
159
0
13
Order By: Relevance
“…However, in a study of BPD patients, depressed mood, but not cooccurring affective disorder, was found to be associated with a history of suicidal behavior (Soloff, Lis, Kelly, Cornelius, & Ulrich, 1994). These results suggest that severity of depressed mood, as assessed subjectively and on a continuum, may be a better predictor of suicide behavior than the MDD diagnosis.…”
mentioning
confidence: 80%
“…However, in a study of BPD patients, depressed mood, but not cooccurring affective disorder, was found to be associated with a history of suicidal behavior (Soloff, Lis, Kelly, Cornelius, & Ulrich, 1994). These results suggest that severity of depressed mood, as assessed subjectively and on a continuum, may be a better predictor of suicide behavior than the MDD diagnosis.…”
mentioning
confidence: 80%
“…SMB has been shown to be related to higher levels of negative affect (Klonsky et al, 2003;Sampson et al, 2004); alcohol use (Roberts et al, 2004;Sansone, 2005); anger and hostility (Herpetz et al, 1997;Soloff et al, 1994); and impulsivity (Kingsbury et al, 1999;Maser et al, 2002;Simeon, 2006). Additionally, age may play an important role in the occurrence of SMB, with a higher incidence of SMB often found among younger individuals (Joyce et al, 2006;Sansone et al, 2002;Schmidtke et al, 1996).…”
mentioning
confidence: 99%
“…L'adolescence jusqu'à la trentaine serait la période de plus haut risque chez ces sujets . En comparaison aux patients souffrant de dépression, l'apparition des conduites suicidaires serait plus hâtive et le nombre de tentatives à vie plus élevé chez les patients présentant un TPL (Soloff, Lis, Kelly, Cornelius, & Ulrich, 1994). Enfin, lorsque le diagnostic de TPL s'ajoute à celui de la dépression, les conduites suicidaires tendent à s'aggraver.…”
Section: Conduites Suicidairesunclassified